(untitled) (Research, Society and Development, 2021)
Diabetes mellitus (DM) is defined as a chronic, non-communicable disease characterized by the presence of chronic hyperglycemia. It can be subdivided into three main types: type 1 DM (autoimmune), type 2 DM (insulin resistant) and gestational DM. DM has become a global public health problem, so there is a need for studies on this disease, in order to improve access to information, research and quality of life for individuals. Therefore, this study aimed to describe the main pathophysiological characteristics associated with type 1 DM. The methodology used was based on the search for scientific papers in the Scielo, Lilacs, BVS, Pumed and Medline databases. In the case of type 1 DM, its main occurrence is due to an autoimmune reaction, generated by the mistaken production of antibodies that "attack" the pancreatic beta cells, thus disrupting the secretion of insulin and, consequently, the absorption of glucose by the cells, generating hyperglycemia. Type 1 DM has its origin in a multifactorial way, involving genetic characteristics, but also being influenced by environmental factors. The clinical and laboratory diagnosis of type 1 DM is made through the analysis of hereditary characteristics as well as the present symptoms, including laboratory data on the patient’s blood glucose, the percentage of HbA1c and specific immunological markers. Therefore, it is clear that the pathogenesis of type 1 DM involves a complex network of physiological and biochemical alterations resulting from the state of chronic hyperglycemia in which the organism finds itself due to the destruction of pancreatic beta cells.